Polygamy in Mormonism: History, Conflicting Doctrines, and Contemporary Perspectives (Departement of Comparative Study of Religions, 2023)
Polygamy is considered the most sacred and crucial doctrine in Mormon belief, revealed to the founding prophet of Mormonism for dissemination to humanity on Earth. In practice, polygamy has reached remarkably high levels, sparking controversy since the 18th century and engendering conflicts between the Mormon Church and the governments of the regions where they reside, causing disadvantages for Mormon followers settled in those areas. This article provides a detailed examination of the practice of polygamy within the Mormon Christian doctrine, deemed the most sacred tenet in their faith. Employing a qualitative approach, the research analyzes literature using a historical method to explore the history of polygamy in Mormon teachings. Additionally, an in-depth analysis is conducted to comprehend the definition, legal basis, conditions, and purposes of polygamous practices within the Mormon community. The research findings indicate a high population level of polygamous practices in the early 18th century, where one man could have dozens of wives. Despite being prohibited in the 19th century, Mormon adherents vehemently maintain this practice. Based on analyses from various sources, this research discovers that polygamy within the Mormon community is regarded as the highest form of marriage. This is due to the overarching goal of Mormon beliefs: to establish the Kingdom of God on Earth. The more polygamous practices, the more individuals born, seen as a contribution to fulfilling the Kingdom of God. The primary principle for engaging in polygamy is to have as many wives as possible, with the aim of liberating unborn spirits.